Classification of strain CCM 4446T as Rhodococcus degradans sp. nov - Švec, Pavel; Černohlávková, Jitka; Busse, Hans-Jürgen; Vojtková, Hana; Pantůček, Roman; Cnockaert, Margo; Mašlaňová, Ivana; Králová, Stanislava; Vandamme, Peter; Sedláček, Ivo (International journal of systematic and evolutionary microbiology, 2015)
Strain CCM 4446T, with notable biodegradation capabilities, was investigated in this study in order to elucidate its taxonomic position. Chemotaxonomic analyses of quinones, polar lipids, mycolic acids, polyamines and the diamino acid of the cell-wall peptidoglycan corresponded with characteristics of the genus Rhodococcus. Phylogenetic analysis, based on the 16S rRNA gene sequence, assigned strain CCM 4446T to the genus Rhodococcus and placed it in the Rhodococcus erythropolis 16S rRNA gene clade. Further analysis of catA and gyrB gene sequences, automated ribotyping with EcoRI restriction endonuclease, whole-cell protein profiling, DNA-DNA hybridization and extensive biotyping enabled differentiation of strain CCM 4446T from all phylogenetically closely related species, i.e., Rhodococcus baikonurensis, Rhodococcus qingshengii, Rhodococcus erythropolis and Rhodococcus globerulus. The results obtained show that the strain investigated represents a novel species within the genus Rhodococcus, for which the name Rhodococcus degradans sp. nov., is proposed. The type strain is CCM 4446T ( = LMG 28633T).
Keywords: mastné kyseliny; kyseliny mykolové; Fatty Acids; Polyamines; DNA bakterií; bakteriální geny; Switzerland; peptidoglykan; RNA, Ribosomal, 16S; kyselina diaminopimelová; DNA, Bacterial; Švýcarsko; fosfolipidy; hybridizace nukleových kyselin; Molecular Sequence Data; Mycolic Acids; Vitamin K 2; půdní mikrobiologie; vitamin K 2; Phylogeny; Peptidoglycan; molekulární sekvence - údaje; Phospholipids; Bacterial Typing Techniques; Soil Microbiology; Sequence Analysis, DNA; ribotypizace; Diaminopimelic Acid; techniky typizace bakterií; Nucleic Acid Hybridization; Rhodococcus; Genes, Bacterial; sekvenční analýza DNA; fylogeneze; RNA ribozomální 16S; polyaminy; Ribotyping